1998
DOI: 10.1002/1529-0131(199807)41:7<1227::aid-art13>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation of osteoarthritis: Data from the Baltimore longitudinal study on aging

Abstract: Objective. To evaluate the familial aggregation of osteoarthritis (OA) in a cohort of healthy volunteers drawn from a community setting.Methods. Hand radiographs obtained between 1978 and 1991 and bilateral standing knee radiographs obtained between 1984 and 1991 were read for changes of OA, using Kellgren-Lawrence (K-L) scales. The hand sites were distal interphalangeal (DIP) joints, proximal interphalangeal (PIP) joints, and first carpometacarpal (CMC1) joints. For each joint group, the presence of OA in at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 9 publications
4
55
1
3
Order By: Relevance
“…In Table 3, the findings of the present study are compared with the findings of the 3 previous studies on the heritability of OA, including a twin study and 2 population-based studies (3)(4)(5). For the sake of comparability, we also calculated sib-sib correlations (Table 3).…”
Section: Discussionmentioning
confidence: 93%
“…In Table 3, the findings of the present study are compared with the findings of the 3 previous studies on the heritability of OA, including a twin study and 2 population-based studies (3)(4)(5). For the sake of comparability, we also calculated sib-sib correlations (Table 3).…”
Section: Discussionmentioning
confidence: 93%
“…It has been demonstrated that genetic factors also play an important role in late-onset OA. Familial aggregation of OA (especially hand, knee, and hip OA) was observed in population-based studies (1)(2)(3)(4). Candidate genes that may exert this genetic influence have been investigated by means of population-based association studies and genetic linkage studies in OA families.…”
Section: Discussionmentioning
confidence: 99%
“…For OA of the knee, no significant correlation was found (r = 0.33); however, as the authors themselves stated, this finding could be due to underestimating of the number of cases of knee OA. The results from this cohort demonstrate familial aggregation of OA and suggest that genes could play a more significant role in severity than in occurrence (Hirsch et al, 1998). This, however, does not exclude a role for environmental influences because the authors did not look for putative environmental factors, as frequently occurs in large-scale studies in which control or ascertainment of all variables is difficult.…”
Section: Population-based Family Studiesmentioning
confidence: 79%